Adsorpsi Ion Logam Cd(II) oleh Selulosa Limbah Sabut Kelapa sebagai Adsorben Berbiaya Murah - SHOFIA KHOERUNNISA SAEF; VINA AMALIA; ADI MULYANA SUPRIATNA (UIN Sunan Gunung Djati Bandung, 2022)
Water will become polluted if the metal content of Cd(II) exceeds the threshold. Cd(II) levels can be reduced by adsorption in water using cellulose as an adsorbent and the adsorbent used is cellulose from coconut fiber. In this study, the synthesis of cellulose from coconut fiber was carried out, then characterized by FTIR and SEM to identify the functional groups and the structure of the coir adsorbent fiber. Subsequently, an analysis was conducted on the effect of the adsorbent performance in absorbing metal ions Cd(II), and the adsorption isotherm model was determined. Cellulose from coconut fiber was synthesized by drying in direct sunlight for 3 days, then activated with NaOH activator for 24 hours, and delignification method was carried out with 8% NaOH. The synthesis results were characterized using FTIR and SEM. Cellulose was applied by batch method on Cd(II) metal with mass variation (0,01-0,05 g), contact time variation (15-60 minutes), pH variation (3-7), and initial concentration variation (0,6-1,4 ppm) and determining the optimum conditions using the AAS instrumentation. Cellulose characterization was identified using FTIR indicating that there are functional groups in the form of C-O and C-O-C bonds, while from the results of SEM analysis, it is known that coconut coir cellulose has fiber for adsorption. Based on the results of the adsorption analysis of cellulose on metal Cd(II) showed the optimum results at an adsorbent mass of 0,05 g for 45 minutes at pH 7 and the initial concentration of Cd(II) used was 0,6 ppm. The isotherm-adsorption of Cd(II) metal on coconut coir cellulose followed the Langmuir isotherm model with R2 of 0,9524